La razón desvalida. Poder y libertad en la obra de Robert Spaemann - Pérez Téllez, Javier Eduardo (2022)
Ratio, as a universal attribute of human being, would be the essential element to establish forms of political praxis deprived of any kind of coercion. The present article aims to introduce the reader to this controversy by means of the considerations made by the philosopher Robert Spaemann. In order to fulfill this objective, we will first explore what made Spaemann involve in the debate. Then, we will study the concept of power and freedom in Spaemann´s work. In the third section of the article, we will explain and discuss our author´s oucome to the controversy. Finally, we will offer some reflections in regard of this subject.